A descriptive analysis of anglicisms used in Ecuadorian newspapers - Hidalgo Garzón, Cesar Alexander (2010)
This study was carried out in Tumbaco which is a valley located next to Quito. The main objective of this research was to make a descriptive analysis of anglicisms used in three Ecuadorian newspapers, and to include etymological, syntactic, lexical-semantic and morphological aspects about anglicisms using the quantitative and qualitative method. The current research was performed using three different Ecuadorian newspapers: a National, a Local and a Tabloid. These three newspapers were chosen in order to find out what the most common anglicisms used in these newspapers were.